Colorectal cancer testing rates after implementation of an organised screening programme in Vaud, Switzerland (Swiss Medical Weekly, 2023)
AIMS OF THE STUDY: Canton Vaud, Switzerland, implemented an organised colorectal cancer  screening programme with colonoscopy and faecal occult blood tests in 2015, 4 to 6 years ahead of neighbouring cantons. Before its implementation, nearly half of Swiss citizens were already up to date with screening, primarily from opportunistic colonoscopies. We hypothesised that earlier implementation of an organised programme would be associated with greater increases in colorectal cancer testing rates.METHODS: We analysed Swiss health insurance claim data from CSS, a Swiss health insurer covering 16% of the Swiss population and 10% of canton Vaud. We stratified 50–69-year-olds into groups from Vaud, its four neighbouring cantons (Fribourg, Geneva, Neuchâtel and Valais), and the rest of Switzerland. We analysed overall, faecal occult blood test and colonoscopy testing rates for each year between 2010 and 2018.RESULTS: The overall testing rate increased from 7.6% in 2010 to 11.6% in 2018 (+4.0%) in Vaud, from 6.1% to 9.3% (+3.2%) in neighbouring cantons and from 7.4% to 8.6% (+1.2%) in the rest of Switzerland. The faecal occult blood test rate increased between 2016 and 2018 from 2.9% to 4.1% (+1.2%) in Vaud and from 1.7% to 2.6% (+0.9%) in neighbouring cantons, but it decreased from 3.1% to 1.5% (–1.6%) in the rest of Switzerland. The colonoscopy rate increased in all cantons, from 4.7% to 7.5% in Vaud (+2.8%), from 4.4% to 6.7% in neighbouring cantons (+2.3%) and from 4.3% to 7.1% in the rest of Switzerland (+2.8%). By 2018, 40% of faecal occult blood tests and 26% of colonoscopies in Vaud occurred in the organised programme. Those who completed an faecal occult blood test within the Vaud programme were younger, had fewer comorbidities and were more likely to have a high-deductible health plan than those tested outside the programme.CONCLUSIONS: Colorectal cancer testing rates increased between 2010 and 2018, with greater absolute increases in Vaud than in neighbouring cantons or the rest of Switzerland. Faecal occult blood test use increased in both Vaud and neighbouring cantons, possibly reflecting changes in testing patterns by general practitioners. By 2018, 40% of colonoscopies and 26% of faecal occult blood tests occurred within the screening programme.